Ethanol Vapor Sensing Property of Quartz Crystal Microbalance Sensor Coated with Carbon Nanotubes. - Nguyen, Duc Hoang; Nguyen, Thanh Vinh; Vu, Van Cat; Nguyen, Van Toan; Dang, Thi Thanh Le; Nguyen, Van Quy (Old Journal, 2019)
In this study, ethanol gas sensor based on a quartz crystal microbalance (QCM) coated with carbon nanotubes (CNTs) was studied. From field-emission scanning electron microscope (FESEM), it was found that the average length and diameter of the CNTs were about 4.52 µm and 75 nm, respectively. Further, carbon nanotube coated on a QCM for ethanol gas sensors were fabricated. The gas-sensitivity of sensor was studied systematically in concentrations of ethanol vapor range from 5 to 25 sccm at room temperature over time. The results show that the sensor has a response time in the range of 200 to 300 seconds and potential application in ethanol gas sensor.